Influence of selected essential amino acid and fatty acid supplementation on growth performance and immune response of broiler chickens challenged with infectious bursal disease virus - Maroufyan, Elham (2012)
Products of poultry are now understood to be vulnerable to contagious diseases and are indicated to affect global industries. According to the research-based evidences shows that infectious bursal diseases (IBD) play a major role in economic losses due to reduced production efficiency, mortality and also the increased usage of antibiotics and chemicals to fight against infections which is a main concern for human health. Therefore, minimizing its impact is an important policy with different strategically approaches for success in the poultry industry. Nutrition is known as a strategy to control immunodeficiency. It is suggested that essential amino acids and fatty acids as immunostimulants are important for animal health. A series of experiments were conducted to examine the effects of essential amino acids and fatty acids as growth and health promotes in broiler chickens challenged by IBD virus. Experiment I was conducted to examine the effects of dietary methionine and threonine levels higher than the National Research Council (NRC) recommendation on growth performance and immune responses of broiler chickens challenged with IBDV. A total of 450 day-old male broiler chicks (Cobb) were housed in 45 pens of 10 birds each until day 42. The dietary treatments were three levels of methionine in the form of DL-methionine; at recommended (M1), double (M2) and triple (M3) NRC levels and three levels of threonine in the form of L-threonine at recommended (T1), double (T2) and triple (T3) NRC levels. There was significant decline in body weight and feed intake in birds subjected to the highest level of threonine and methionine but highest antibody titers and also the lowest lesion score were obtained in broilers receiving M2T3 and M3T3. Performance and immune responses of chickens fed with two folds of methionine (M2T1) were significantly (P<0.05)better than other treatment. The results obtained in the present study indicated that threonine and methionine requirements of broilers based on the recommendations of NRC did not give the maximum response. Experiment II was conducted to examine the effects of tuna fish oil and sunflower oil as sources of n-3 and n-6 PUFA on growth performances, fatty acid profiles and immune responses to IBDV challenged broiler chickens. Commencing from day one, five replicate pens of 15 one-day-Cobb male chicks each were assigned to one of the five dietary treatments, giving a total of 25 pens for 42 days. The dietary treatments were: 1) Basal diet (NRC) (C), (2) Basal diet containing 5.5% tuna oil + 0.5% sunflower oil (VL), 3) Basal diet containing 4% tuna oil + 2% sunflower oil (L), 4) Basal diet containing 2.5% Tuna oil + 3.5% sunflower oil (H) and 5) Basal diet containing 1.5% tuna oil + 4.5% sunflower oil (VH). The lowest feed conversion ratio of 1.94 (P<0.05) was observed in birds treated with H group. The birds fed VH group had lowest level of Interferon-gamma (IFN-) at 2 d post challenge ((P<0.05). The increase in n-3 PUFA levels significantly (P<0.05) tended to enhance Interlukin-2 (IL-2) as well as antibody titers production in IBDV challenged broiler chickens. Therefore, an ideal fatty acid profile should be maintained in the diet to improve the broiler chickens’ immune system. Experiment III was conducted to examine the response of IBDV challenged broiler chickens receiving different dietary ratios of n-6 to n-3 PUFA and supplementation of methionine on performance and immunity. A total of 350 one-day-old male broiler chicks (Cobb 500) were assigned to one of the six dietary treatments, giving a total of 35 cages. There were three ratio of n-6: n-3 PUFA [(45 (N1), 1.1 (N2) and 4.19 (N3)] and two levels of methionine in the form of DL-methionine [NRC (M1), 2 times NRC (M2)]. The birds aged 0-21 days were fed diets containing graded concentrations of methionine (0.25 and 0.80% of diet) similarly graded concentrations of methionine (0.23% and 0.74% of diet) to birds aged 22-42 days. Therefore, six dietary treatments were compared: 1) Basal diet based on NRC recommendation (M1N1), 2) Basal diet containing methionine 2 fold higher than NRC (M2N1), 3) Basal diet containing 5.5% tuna oil + 0.5% sunflower oil (M1N2), 4) Basal diet containing 2.5% tuna oil + 3.5% sunflower oil (M1N3), 5) Combination of diet 2 and 3 (M2N2) and 6) Combination of diet 2 and 4 (M2N3). A second control group served as IBDV-unchallenged group (CON) in this study. Prechallenge performance data indicates that body weight gain and feed conversion ratios significantly affected by the interaction between the methionine levels and n- 6: n-3 PUFA ratios. A mean body weight gain of 1411 g was highest at weeks 4 in birds treated with M2N3 group with an improved feed conversion ratio of 1.48 at pre challenged period. However, there was no any interaction between methionine and n-6: n-3 PUFA in broilers subjected to immunological challenge (P < 0.05). An antibody titer of 4.15 ng/ml and 4.04 ng/ml was significantly (P < 0.05) higher in birds fed a low ratio of n-6: n-3 PUFA (N2) than the other groups at 7 and 14 days after challenge. When methionine × n-6: n-3 PUFA ratio interaction was significant,the IL-2 level of M1N2 and INF- level of M2N1 were higher than other groups on 2 days and 7 days post-challenged, respectively. On d 28, serum cholesterol levels were significantly lowered (2.5mmo/L) in the birds treated with N2M1 (P<0.05). A significant improvement (P<0.05) in lesion score was observed in N2,N3 group on 7 days post-challenged and M2 group on 14 days post-challenged (P<0.05). Therefore, this study emphasizes those changes induced by the amount of n-6: n-3 fatty acid ratio may be supplied to the human diet as a result of consuming a portion of fat-modified chicken meat. In conclusion, current studies demonstrated that increasing the dietary methionine level up to two-fold of NRC (1994) standards is required to achieve adequate growth, feed conversion ratio and optimal immunity in IBD challenged broiler chicken. Dietary n-3 PUFA enrichment may improve the immune response and IBD resistance, but the optimum performance does not coincide with the optimum immune response. It seems that dietary n-3 PUFA modulates the broiler chicken performance and immune response in a dose-dependent manner. Thus, a moderate level of dietary n-3 PUFA enrichment may help to put together the efficiency of performance and relative immune response enhancement in broiler chickens.Further, although there was no interaction between high level of methionine and ratio of n-6:n-3 PUFA for performance parameters, humeral immunity and lesion score of bursa in broilers subjected to immunological challenge, the individual roles of n-6:n-3 PUFA ratio and methionine on bursa lesion reduction and/or antibody production are documented. Therefore, a balanced intake of both n-6 and n-3 fatty acid combined with methionine supplementation have the potential to promote performance and improve the broiler chicken immune system. Moreover, supplementation of fish oil in broiler diet may be considered as a functional practice to produce n-3 PUFA enriched meat with optimum n-6:n-3 PUFA ratios with regards to human health.